2023
DOI: 10.1021/acs.inorgchem.3c00228
|View full text |Cite
|
Sign up to set email alerts
|

Dioxygen Activation by a Bioinspired Tungsten(IV) Complex

Abstract: An increasing number of discovered tungstoenzymes raises interest in the biomimetic chemistry of tungsten complexes in oxidation states +IV, +V, and +VI. Bioinspired (sulfur-rich) tungsten(VI) dioxido complexes are relatively prevalent in literature. Still, their energetically demanding reduction directly correlates with a small number of known tungsten(IV) oxido complexes, whose chemistry is not well explored. In this paper, a reduction of the [WO 2 (6-MePyS) 2 ] (6-MePyS = 6-methylpyridine-2-thiolate) comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Such a dimeric species would undergo swift decomposition to Int 1 and the corresponding dioxido complex [WO 2 (6-MePyS) 2 ], the latter being the driving force of the overall process due to the thermodynamically favorable WO bond formation . The formation of [WO 2 (6-MePyS) 2 ] has been indirectly confirmed via its decomposition products in the presence of water, which are protonated ligand 6-MePySH and undefined [WO 3 ] n species . An independent NMR study confirmed the formation of [WO 3 ] n species from the dioxido complex under aqueous basic conditions (see SI).…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Such a dimeric species would undergo swift decomposition to Int 1 and the corresponding dioxido complex [WO 2 (6-MePyS) 2 ], the latter being the driving force of the overall process due to the thermodynamically favorable WO bond formation . The formation of [WO 2 (6-MePyS) 2 ] has been indirectly confirmed via its decomposition products in the presence of water, which are protonated ligand 6-MePySH and undefined [WO 3 ] n species . An independent NMR study confirmed the formation of [WO 3 ] n species from the dioxido complex under aqueous basic conditions (see SI).…”
Section: Resultssupporting
confidence: 64%
“… 32 The formation of [WO 2 (6-MePyS) 2 ] has been indirectly confirmed via its decomposition products in the presence of water, which are protonated ligand 6-MePySH and undefined [WO 3 ] n species. 33 An independent NMR study confirmed the formation of [WO 3 ] n species from the dioxido complex under aqueous basic conditions (see SI ). Quantitative conversion of the starting complex to styrene indicates that the vinyl intermediate Int 1 must react with 6-MePySH to recover one equivalent of complex 3 .…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…120 The same compound also catalyzes the oxidation of triphenylphosphine using oxygen as the terminal oxidant. 121…”
Section: Discussionmentioning
confidence: 99%
“…120 The same compound also catalyzes the oxidation of triphenylphosphine using oxygen as the terminal oxidant. 121 Oxidative bromination analogous to the cases involving molybdenum dioxo complexes (vide supra, Scheme 6) have been reported for a few tungsten dioxo complexes. 122…”
Section: Dalton Transactions Perspectivementioning
confidence: 96%